"A mild despotism of sugar": Race, labor, and flood management in British Guiana. Issue 99 (February 2019) - Mullenite, Joshua
Highlights: Critically examines the racialized and class-based histories of flood control. Develops explicit connections between critical race and infrastructure studies. Highlights environmental basis of colonial governance strategies. Abstract: Volumes of research have demonstrated the ways in which the production of sugar served as a key economic motivator for the development of capitalism. Embedded within this extractive economy is a requirement for strict environmental management and large pools of seasonal labor, typically within the context of the racial geographies of colonialism. In this article, I draw on archival research conducted at the National Archives in London, UK to examine the relationship between these agrarian economies, the social and economic requirements for flood control on a low-lying coastal plain, and British colonial-racial politics in British Guiana. I argue that colonial planters manipulated flood control systems and legislation in a way that produced and maintained a reserve army of black labor and in the process producing a racial geography meant primarily to ensure the survival of the crop even as prices plummeted in the twentieth century.